Non-Candida mycosis in Gulf Cooperation Council (GCC) countries: perspective of a low-incidence region - Abdullah AlSaleh; Mohammed Shahid (BMC Infectious Diseases)
Abstract Background Fungal pathogens are ubiquitous microorganisms that are implicated in a wide range of infections, affecting individuals with underlying health conditions and immune suppression therapy; however, immunocompetent individuals may also be at risk. Among these infections, many are caused by molds and yeasts other than Candida and are recognized in clinical practice, such as aspergillosis, mucormycosis, fusariosis, phaeohyphomycosis, and basidiobolomycosis, among others, each presents different clinical manifestations and requires clinical management specific to the site of involvement. Although pathogenic fungal contaminants and potential sources of mycosis in humans are plentiful in Gulf Cooperation Council (GCC) countries, epidemiological reports regarding mycosis in the region are scarce. Aim The aim of this review is to shed some light on the epidemiology of clinically associated molds and yeasts other than Candida and to survey all related case reports and epidemiological studies conducted in the GCC over the past 10 years. Methods A comprehensive search of the Medline (PubMed) and Scopus databases was conducted using the following keywords: Aspergillosis, Mycosis, Mucormycosis, Fusarium, Kuwait, Bahrain, Saudi Arabia, Qatar, Oman and the United Arab Emirates. A timeframe was set to include only articles that were published from 2014 to 2024. Results One hundred thirty-five of the 1563 articles examined fulfilled the purpose of this review. Most studies were in Saudi Arabia (45%), Qatar (18%) and Kuwait (16%). Mucormycosis, aspergillosis, phaeohyphomycosis and basidiobolomycosis were among the most commonly reported fungal infections in the GCC, with corresponding mortality rates of 53%, 37%, 69% and 24%, respectively. The average estimations of non-Candida fungal infections indicate a low regional incidence in comparison with global estimations. Conclusion Awareness and a high index of suspicion are warranted in successfully managing non-Candida mycosis. More specific immunological and molecular markers are needed for differential diagnosis to rule out fungal infections. Additionally, incorporating non-Candida mycosis-related antifungal resistance surveys in GCC national surveillance efforts should be enforced, especially when considering the increase in global mycosis rates.